Impact of pharmacist-prescriber partnerships to track antibiotic prescribing in publicly funded primary care in the Cape Town Metropole, South Africa: an implementation study - Prof Oliver Van Hecke; Dr Yusuf Adegoke; Prof Klaus von Pressentin; Prof Mosedi Namane; Prof Marc Mendelson; Prof Chris Butler; Prof Renier Coetzee (International Journal of Infectious Diseases)
Introduction: There is limited published data of antibiotic prescribing for common infections managed in primary care in South Africa, especially in the public sector. This is a fundamental evidence gap. Where prescribing data are available, these data are retrospective and not linked to clinical indication. Methods: The PRINS Study is a prospective observational study across 5 clinics in the Cape Town Metropole. We employed a prescriber-pharmacist partnership at each clinic to gather prospective antibiotic prescribing data for ‘acute cough’, linked to clinical indication, and provided individual prescribing feedback about prescribing quality (antibiotic dose, duration, dose frequency) through each clinic's WhatsApp group. Results: Eight out of every 10 patients were prescribed an antibiotic for ‘acute cough’ (n=457). In 35% of cases, an antibiotic was prescribed for a clinical diagnosis of ‘community-acquired pneumonia’. Half of all recorded antibiotics were prescribed by nurse prescribers where there was no pharmacist oversight. The proportion of pharmacy dispensed antibiotics concordant with local guidelines in terms of antibiotic dose, duration and frequency was 95% [95% CI 0.93 to 0.98], n= 239). In terms of quality indicator prescribing against AWaRe guidance, 97% of antibiotics prescribed belonged to the ‘Access’ group. Discussion: This study captured prescribing data, linked to clinical indication, using a multidisciplinary pharmacist-prescriber approach. This aligns with the findings in a systematic review which showed that the pharmacist-prescriber model can effectively increase guideline-adherent antibiotic prescribing. However, the studies included in the review were all conducted in high-income countries. This study is the first attempt in Africa to utilise this partnership in publicly funded primary care. We included both nurse- and doctor prescribers to reflect the breadth of antibiotic prescribing practice in the region, recognising that nurses see most patients. Our team-based approach to collecting these data ensured that we used limited resources advantageously and empowered prescriber-pharmacist teams to co-design and participate in the study. Conclusion: This study provides key data to accurately assess what problems there are in terms of access to, and excess of, antibiotics across the region. The data generated from PRINS has filled an evidence gap that will inform antibiotic stewardship innovations and future interventions by mapping usual clinical care for patients presenting with acute cough.